Tecnologias digitais no processo ensino-aprendizagem : habilidades necessárias para a construção do conhecimento científico no estado de Roraima - Silva, Wender Antônio da (2018)
Considering the 21st century technological scene, the information society, the concepts of natives and digital immigrants, and aspects related to the educational challenges of applyng methodological strategies that can use digital technologies as an auxiliary resource in the classroom in the teaching- learning process, the work try to answer the following problem of scientific research: how can digital technologies influence the development of skills in the teaching-learning process that make possible the construction of scientific knowledge? To solve this scientific problem, the following thesis is presented: the constant evolution of digital technology in the information society in the 21st century influences the context of the teachinglearning process, enabling the development of skills for the construction of scientific knowledge and, in this sense, it is sought to identify how digital technologies facilitate the development of skills for the construction of scientific knowledge. For this, it was verified with students and professors of the science courses, in the modality of physical education (Biology, Chemistry, Physics, Mathematics and Natural Sciences), in a public college in Roraima, Brazil, which would be the skills in technologies digital questionnaires that each group of the sample presented, whether in the academic, personal and professional questions, and in this way a questionnaire based on Likert was applied with a sample of 173 students, interviews were carried out with 14 teachers and, later, another questionnaire was applied based on Guttman for 76 students. The approach of the research is mixed, being carried out statistical treatment in the questionnaires, analysis of the national curricular guidelines and of the pedagogical projects of course and transcription and analysis of the content of the interviews. After analyzing the results, a set of strategies was developed (matrix of skills and competences, systemic model and theoretical model) to guide professors to use digital technologies as a support tool in the teaching-learning process, which can lead the improvement of the scientific knowledge process.